PERAN GUBERNUR SEBAGAI WAKIL PEMERINTAH PUSAT DALAM MELAKSANAKAN PEMBINAAN DAN PENGAWASAN ATAS PENYELENGGARAAN PEMERINTAHAN DAERAH BERDASARKAN UNDANG UNDANG NOMOR 32 TAHUN 2004 - Herma Yanti (Jurnal LEX SPECIALIS, 2012)
Abstract Guidance and supervision by the central government to local government penyelenggraaan is an important aspect in order to guarantee the upholding of the Republic of Indonesia. for the governance of the district / city, in order to ensure an effective and efficient the Act No. 32 of 2004 puts Governor as Deputy Regional Government in addition to his position as head of the province. To that end, the governor has a very important role that local government penyelenggaraaan not deviate from the concept of the Unitary Republic of Indonesia, as well as guaranteeing the compatibility and harmony between government actions government structure. But the governor's role as the representative of the central government is weak, because it implies a relationship disharmony between the governor and the district / city. This was influenced by the provisions of Law No. 32 of 2004 that put the governor on the dual position as head of the region as well as representatives of the central government in the region, as well as setting the position of governor as the representative of the central government were inadequate. Key Note : Development of Local Government Supervision